1996
DOI: 10.1210/endo.137.2.8593830
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oxytocin receptor in human pregnant myometrium.

Abstract: Around the onset of labor, uterine sensitivity to oxytocin (OT) increases tremendously. Although this is considered to reflect OT receptor (OTR) augmentation in myometrium, neither spatial expression of OTR nor the level of the receptor message during the course of pregnancy have been investigated at the molecular level. We examined the localization and expression of the OTR in human myometrium by means of in situ hybridization, immunohistochemistry, and Northern and Western blotting. In the term pregnant myom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(73 citation statements)
references
References 1 publication
5
67
0
1
Order By: Relevance
“…Oxytocin is a well-known neurohypophysial hormone that facilitates parturition and is commonly used as an uterotonic drug in clinical practice for the treatment of primary postpartum haemorrhage. Many studies have demonstrated that OTR level in myometrium is much higher at the end of pregnancy, which is critical for the onset of labour (Fuchs et al 1995, Kimura et al 1996, Challis et al 2000 although a few studies reported that OTR expression is not increased with labour (Phaneuf et al 2000, Havelock et al 2005. This study confirmed the previous findings that PGF2A upregulates the expression of these proteins in human pregnant myometrium, suggesting that PGF2A is involved in the processes of uterus activation for labour.…”
Section: Discussionsupporting
confidence: 87%
“…Oxytocin is a well-known neurohypophysial hormone that facilitates parturition and is commonly used as an uterotonic drug in clinical practice for the treatment of primary postpartum haemorrhage. Many studies have demonstrated that OTR level in myometrium is much higher at the end of pregnancy, which is critical for the onset of labour (Fuchs et al 1995, Kimura et al 1996, Challis et al 2000 although a few studies reported that OTR expression is not increased with labour (Phaneuf et al 2000, Havelock et al 2005. This study confirmed the previous findings that PGF2A upregulates the expression of these proteins in human pregnant myometrium, suggesting that PGF2A is involved in the processes of uterus activation for labour.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier studies have reported that OT (37) and its receptor are expressed in normal human endometrial and myometrial cells (12,(36)(37)(38)(39)(40). In addition, a role of OTR and VPR in the pathogenesis of dysmenorrhea and development of dyscontractile disorders have also been supported (7,8,41).…”
Section: Discussionmentioning
confidence: 93%
“…It is a key regulator of myometrial function. Its expression increases with advancing gestation (Fuchs et al 1991), peaking in early labour (Rivera et al 1990), corresponding to the clinical observation of increased uterine sensitivity to OT (Kimura et al 1996). OT increases myometrial contractility via increases in intracellular calcium, mediated through its G-protein-coupled receptor, OTR.…”
Section: :3mentioning
confidence: 99%